(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The title Schiff base LH obtained by the reflux condensation of 2-hydroxy-1,4-napthoquinone and 2-amino-3-hydroxypyridine has been characterized via conventional procedures. Adsorption and corrosion inhibition potentials of LH were examined by considering its inhibitory efficiency on mild steel in 1M HCl via weight loss assessment, scanning electron microscopy and density functional theory. Analytical and spectroscopic methods corroborate the bidendate ketoimine-tautomeric assemblage of LH and its stability at ambient temperature. The weight loss measurement was performed at mixt temperatures of 303-343 K and inhibitor concentrations of 1x10-5 M- 9x10-5 M with immersion period of 5 h. Higher efficiency of 94.6% was attained with an inhibitor concentration of 9x10-5 M at 303 K. The adsorption of LH on mild steel (ms) was found to conform with Langmuir absorption isotherm model, while free energy of adsorption showed a spontaneous physiosorption. The computed activation energy (Ea) along other thermodynamic parameters (Î”S and Î”H) was consistent with the latter. The SEM results revealed that the ms superficial was smooth with the inhibitor compared to the ms superficial without the inhibitor indicating inhibition of corrosion of the ms by establishing a layer of protection on the surface. The density functional theory result was in agreement with experimental results.